2005
DOI: 10.1016/j.giq.2005.05.002
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on the impact of quality antecedents on tax payers' acceptance of Internet tax-filing systems

Abstract: This study used the Technology Acceptance Model (TAM) to examine taxpayers' acceptance of the Internet tax-filing system. Based on data collected from 141 experienced taxpayers in Taiwan, the acceptance and the impact of quality antecedents on taxpayers' perceived usefulness (PU) and perceived ease of use (PEOU) of the system were assessed and evaluated. The results indicated that the model of Internet tax-filing system was accepted with a reasonable goodness-of-fit. Three important findings include the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
93
3
12

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(122 citation statements)
references
References 50 publications
(73 reference statements)
14
93
3
12
Order By: Relevance
“…This suggests that; User experience has a significant influence on users' attitude towards the system. This is consistent with previous research findings (Taylor & Todd, 1995;Agarwal & Prasad, 1999;Fusilier & Durlabhji, 2005;Lee, Qu & Kim, 2007) which contends previous exposure to a system, or relative system, is likely to have a positive influence on the constructs measured in the TAM, particularly in relation to PU (Chang et al, 2005), albeit at times, indirectly through increased user self-efficacy (McFarland & Hamilton, 2006).…”
Section: (1) User Experience -Fig 5asupporting
confidence: 91%
“…This suggests that; User experience has a significant influence on users' attitude towards the system. This is consistent with previous research findings (Taylor & Todd, 1995;Agarwal & Prasad, 1999;Fusilier & Durlabhji, 2005;Lee, Qu & Kim, 2007) which contends previous exposure to a system, or relative system, is likely to have a positive influence on the constructs measured in the TAM, particularly in relation to PU (Chang et al, 2005), albeit at times, indirectly through increased user self-efficacy (McFarland & Hamilton, 2006).…”
Section: (1) User Experience -Fig 5asupporting
confidence: 91%
“…Davis's (1989) model, the TAM, is used to evaluate a user's acceptance of a technology. Previous studies have confirmed the applicability of using the aforementioned constructs to research e-government adoption (Carter and Blanger, 2005;Chang et al, 2005;Hung et al, 2006).…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 70%
“…Trust in the internet is one of the main factors highlighted as significant in investigating e-government adoption in both developed and developing countries (AlShafi and Weerakkody 2008;Carter and Bélanger 2005;Carter et al, 2011;Chang et al , 2005). Trust in the internet is often identified as institution-based trust which is "the belief that needed structural conditions are present (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of online tax system by taxpayers is increasing because it is convenience, cost effective and time saving [18]- [20]. Accordingly, the use of online tax system as a new information technology is to achieve an effective tax admiration system.…”
Section: Literaturementioning
confidence: 99%